The Contribution of Health Advocates in Strengthening Community Participation in Preventive Health Programs - Lestari, Diah Ayu; Rahmiati; Aulia, Nur (Generasi Sains Indonesia, 2025)
Community participation is an essential component of effective preventive health programs, yet many communities continue to experience low engagement due to limited health literacy, sociocultural barriers, and inadequate access to health information. This study aims to analyze the contribution of health advocates in strengthening community participation in preventive health programs. A quantitative correlational design was employed involving 210 respondents selected through stratified random sampling from community-based preventive health initiatives. Data were collected using structured questionnaires and analyzed using descriptive statistics, Pearson correlation, and multiple regression analysis. The findings reveal a strong positive relationship between health advocate activities and community participation, indicating that educational outreach, counseling, and mobilization significantly enhance preventive health engagement. Health advocate activity remained the strongest predictor of participation even after controlling for demographic variables, while educational attainment also showed a significant influence on participation levels. The novelty of this study lies in its use of a predictive quantitative framework to empirically measure the contribution of health advocates within preventive public health systems. The study implies that strengthening institutional support, advocacy training, and culturally responsive communication strategies is essential for improving the sustainability, inclusiveness, and effectiveness of preventive health programs.